Cystoprostatectomy versus prostatectomy alone for locally advanced or recurrent pelvic cancer. Issue 1 (12th August 2014) - Turner, Greg A.; Harris, Craig A.; Eglinton, Tim W.; Wakeman, Chris J.; Kueppers, Frank; Dixon, Liane; Dobbs, Bruce R.; Frizelle, Frank A.
Abstract: Background: There is minimal published data evaluating the oncological outcome of rectal resection with prostatectomy alone versus rectal resection with cystoprostatectomy in patients undergoing pelvic exenteration for locally advanced or recurrent pelvic cancer. This study aims to evaluate the oncological and functional outcomes of performing rectal resection with prostatectomy alone compared with rectal resection with cystoprostatectomy in patients undergoing pelvic exenteration. Methods: Consecutive patients undergoing pelvic exenteration for locally advanced or recurrent pelvic cancer between 1998 and 2012 were identified from a prospectively maintained database. Patients undergoing rectal resection with prostatectomy alone were compared with a control group who underwent rectal resection with cystoprostatectomy and urostomy formation. The primary outcome was overall survival. Secondary outcomes analysed in the prostatectomy group included completeness of resection, continence and erectile function. Results: Eleven rectal resections with prostatectomy were compared with 20 rectal resections with cystoprostatectomy. R0 resection was achieved in 73 and 65% respectively. There was no difference in overall survival ( P = 0.40). Urinary continence was achieved in 36% of prostatectomy alone patients, while 27% experienced mild incontinence. Erectile function was poor, with only one patient able to maintain normal erections. Conclusion: In appropriately selected patients with invasive pelvic tumours, rectal resection with prostatectomy alone provides adequate oncological outcomes. The ability to achieve an R0 resection was not compromised and overall survival is comparable with cystoprostatectomy. Urinary function is reasonable in most patients, although sexual function is compromised in almost all.